State-media relations in post-apartheid South Africa - Adrian Hadland (Communicare)
In 2004, Daniel Hallin and Paolo Mancini published a landmark work of media theory entitled Comparing media systems: three models of media and politics. The theory, like the models it makes use of, has a high degree of relevance for South African media scholars. Primarily, the theory investigates the relationship between the state and the media, an interconnection of profound significance in the South African context, yet one that has not been explored sufficiently by scholars. This article, which focuses primarily on South Africa’s print media sector, sets out the parameters, major dimensions and some indicators of the Three Models paradigm. It then presents recent research in which the theory is applied to South Africa. It concludes that South Africa’s media system falls largely into the Polarised Pluralist model though it retains strong liberal model traits